Industrial analysis and determination method of composite iron coke

By using potassium dichromate titration method, atomic absorber and infrared analysis, the various components of composite iron coke are accurately measured, and the problem of inaccurate measurement in the prior art is solved, and accurate feeding basis is provided, which reduces the pig iron cost.

CN119199011APending Publication Date: 2024-12-27新余钢铁股份有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411477692.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The prior art cannot accurately determine the content of all iron, metal iron, ferrous oxide and ash in the composite iron coke, and the measurement results are inaccurate due to the influence of carbon in the composite iron coke.

Method used

Using potassium dichromate titration method, atomic absorber detection, infrared carbon sulfur analysis method and ICP spectrometer, combined with specific sample processing and filtration steps, the total iron, metal iron, FeO, C, and trace elements in the composite iron coke are accurately measured. , SiO2, Al2O3, air-drying base moisture and dry-based volatile components, the influence of these substances is taken into account when calculating the ash content.

Benefits of technology

The accurate measurement of each component of composite iron coke is achieved, and the accurate feeding basis is provided, the cost of pig iron is reduced and the reliability of the measurement results is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005096547820000081
    Figure BDA0005096547820000081
  • Figure BDA0005096547820000121
    Figure BDA0005096547820000121
  • Figure BDA0005096547820000131
    Figure BDA0005096547820000131
Patent Text Reader

Abstract

The invention provides an industrial analysis and determination method of composite ferrocoke, test items comprise the contents of total iron, metallic iron, FeO, C, trace elements, SiO2, Al2O3, air dry basis moisture, dry basis volatile components and ash in the composite ferrocoke, carbon, iron and iron oxides contained in the composite ferrocoke are fully considered in the method, the interference of C is eliminated in determination of total iron, metallic iron and FeO, and the content of trace elements in the composite ferrocoke is determined. When the ash content is calculated, the influence of the substances is considered, so that the ash content and other test items of the composite iron coke are accurately measured, and an accurate basis is provided for feeding calculation of the composite iron coke.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of analysis and testing, and in particular relates to an industrial analysis and determination method for composite ferrocoke. Background Art

[0002] Composite iron coke is a product obtained by hot pressing iron ore powder, bituminous coal and anthracite into flat balls and then roasting them in a carbonization shaft furnace. It is a new type of raw fuel for blast furnaces. As a highly active composite material, iron coke can reduce the initial gasification temperature of coke in the blast furnace, the temperature of the heat storage area, the heat loss in the high-temperature area and the total fuel consumption per ton of iron, which is of great significance to energy conservation and emission reduction; using coal instead of coke can reduce the cost of pig iron.

[0003] Composite ferrocoke can be used as a new type of raw fuel for blast furnace ironmaking. The accurate determination of its chemical composition determines its use value. Regardless of whether composite ferrocoke is used to replace coke or ore, its chemical composition must be taken into account for cost-effectiveness calculation, so as to accurately calculate whether the cost of pig iron can be reduced and how much the cost of pig iron can be reduced.

[0004] However, there is no detection method for composite iron coke in the prior art. At present, the ash content of composite iron coke is usually determined by referring to the determination method of coke, see GB / T 2001-2013 "Industrial Analysis and Determination Methods for Coke" for details. The total iron (TFe) is determined by GB / T 6730.65-2009 "Determination of total iron content in iron ore by titanium trichloride reduction potassium dichromate titration (conventional method)", and FeO is determined by GB / T6730.8-2016 "Determination of ferrous content in iron ore by potassium dichromate titration".

[0005] When using the above-mentioned existing method to determine the total iron, metallic iron and ferrous oxide contents in composite iron coke, accurate results will not be obtained, because due to the influence of the composite iron coke C, the endpoint cannot distinguish whether the titration is complete; when using the above-mentioned existing method to determine the ash content in composite iron coke, the ash content calculation is inaccurate, because the sample is a composite component containing iron and iron oxides, when placed in a muffle furnace for heating, the metallic iron will be oxidized into FeO and Fe2O3, and FeO and Fe3O4 will be oxidized into Fe2O3. The ash content of the product after burning after removing the metallic iron and iron oxides is inaccurate. Summary of the invention

[0006] In order to solve the above technical problems, the present invention provides an industrial analysis and determination method for composite iron-coke, which can accurately determine the content of each component in the composite iron-coke.

[0007] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0008] An industrial analysis and determination method for composite iron coke, the determination method comprising the following test items:

[0009] (1) Determination of total iron content: Grind the composite iron coke, remove moisture, burn and dissolve a quantitative sample, and titrate with potassium dichromate;

[0010] (2) Determination of metallic iron content: Grind the composite iron coke to remove moisture, react a quantitative sample with a copper sulfate solution, and filter it using absorbent cotton. The resulting filtrate is tested by an atomic absorption spectrometer.

[0011] (3) Determination of FeO content: Mix a quantitative sample with sodium bicarbonate and sodium fluoride, isolate the sample from air, add concentrated hydrochloric acid to dissolve the sample, and then filter it with absorbent cotton. The filtrate is titrated with potassium dichromate.

[0012] (4) C content determination: using infrared carbon-sulfur analysis method, the sample is mixed with tin particles and tungsten particles and tested with an infrared carbon-sulfur instrument;

[0013] (5) Trace element determination: The sample is burned, dissolved, fixed to volume, and then detected using an ICP spectrometer;

[0014] (6) Determination of SiO2 and Al2O3: Mix the sample with sodium peroxide after burning, then burn and dissolve it. After cooling, add deionized water and hydrochloric acid solution to make up the volume, and then use ICP spectrometer for detection;

[0015] (7) Determination of air-dried basis moisture: Dry a certain amount of sample in a blast drying oven, and calculate the mass fraction of air-dried basis moisture based on the mass before and after drying;

[0016] (8) Determination of volatile matter on dry basis: Determination shall be carried out in accordance with the method for determination of volatile matter in GBT 212-2008 Industrial analysis method for coal;

[0017] (9) Ash content determination: Ash mass fraction = 100 - C mass fraction - Fe mass fraction - FeO mass fraction - Fe2O3 mass fraction - dry volatile matter mass fraction. Fe2O3 mass fraction = (total Fe mass fraction - FeO mass fraction / 1.2865 - Fe mass fraction) × 1.4296.

[0018] The method for determining the total iron content is as follows: grinding the composite iron coke into 140 mesh particles and drying to remove moisture; accurately weighing a certain mass of the composite iron coke and calcining it at 810-820° C. for 25-35 minutes; dissolving the calcined sample using mixed acid, and after white smoke comes out of the sample, adding hydrochloric acid and tin chloride in sequence, and then titrating with potassium dichromate until the solution turns purple, and calculating the mass fraction of the total iron according to the concentration of potassium dichromate and the volume consumed in the titration.

[0019] Mass fraction of total iron (%): TFe = c × (V-V0) × 55.85 × 100 / (m × 1000)

[0020] Where: molar mass of iron in grams per mole (g / mol).

[0021] c—concentration of potassium dichromate standard titration solution, in moles per liter (mol / L);

[0022] V—volume of potassium dichromate standard titration solution consumed by titrating the sample solution, in mL (mL);

[0023] V0—the volume of potassium dichromate standard titration solution consumed by titrating the blank test solution, in mL (mL);

[0024] m—mass of the sample, in grams (g).

[0025] Furthermore, the mixed acid is a mixed solution of sulfuric acid, phosphoric acid and water in a volume ratio of 3:3:4.

[0026] The method for determining the metallic iron content is as follows: grinding the composite iron coke into 140 mesh particles, drying to remove moisture; accurately weighing a certain mass of the composite iron coke, mixing it with deionized water and copper sulfate solution, heating and boiling for 10 to 20 minutes, then filtering it with absorbent cotton, collecting the filtrate and detecting it with an atomic absorption spectrometer; mixing a series of concentrations of ferric oxide standard solutions with copper sulfate solution, constructing a standard curve with atomic absorption spectrometer detection, and calculating the metallic iron content based on the standard curve.

[0027] The method for determining the FeO content is as follows: uniformly mixing a certain amount of composite iron coke with sodium bicarbonate and sodium fluoride, adding concentrated hydrochloric acid to dissolve the sample, then filtering with absorbent cotton, titrating the obtained filtrate with potassium dichromate until the solution turns purple, and calculating the mass fraction of FeO according to the concentration of potassium dichromate and the volume consumed in the titration.

[0028] Mass fraction of FeO (%): ω Fe(Ⅱ) =((V3-V0)×c×M / m0×10 3 )×100-3ω MFe

[0029] Where:

[0030] c——concentration of potassium dichromate standard titration solution, in moles per liter (mol / L);

[0031] V3——The volume of potassium dichromate standard titration solution consumed by the titration sample solution, in mL (mL);

[0032] V0——The volume of potassium dichromate standard titration solution consumed by titrating the blank test solution, in mL (mL);

[0033] m0——mass of the sample, in grams (g);

[0034] M – molar mass of iron in grams per mole (g / mol);

[0035] ω MFe ——Metallic iron content of the sample, expressed as mass fraction (%).

[0036] The method for determining the C content is: using infrared carbon-sulfur analysis, weighing 0.05g of sample, adding 0.3g of tin particles and 1.5g of tungsten particles, detecting with an infrared carbon-sulfur instrument, and analyzing the results using a calibration curve.

[0037] The method for determining the trace elements is as follows: weigh 0.2 g of a sample and burn it at 815° C. for 30 min. After cooling to room temperature, add 10 mL of hydrochloric acid, 2 mL of nitric acid, 0.5 mL of hydrofluoric acid, and 5 mL of perchloric acid to dissolve the sample until thick perchloric acid smoke is emitted for 1-2 min. Take the sample out and cool it to room temperature. Add 5 mL of HCl to make up the volume. Then, use an ICP spectrometer to detect the sample and analyze the results using a calibration curve.

[0038] The method for determining SiO2 and Al2O3 is as follows: weigh 0.2g of the sample and calcine it in a porcelain square dish at a constant temperature of 815°C for 60min, cool it to room temperature to obtain a powder, then transfer it to a 30mL nickel crucible, add 2g of sodium peroxide, stir evenly, put it into a muffle furnace and heat it at a constant temperature of 815°C for 2-3min to completely dissolve the sample, and cool it to room temperature; add 50mL of deionized water to the sample, mix concentrated hydrochloric acid and deionized water in a volume ratio of 1:4 to obtain a hydrochloric acid solution, then add 40mL of the hydrochloric acid solution to the sample, add deionized water to make the volume up to 200mL, and detect it using an ICP spectrometer.

[0039] The method for determining the moisture content on an air-dried basis is as follows: weigh 1 g ± 0.05 g of an analytical sample with a particle size of less than 0.2 mm and spread it evenly in a weighing bottle, open the weighing bottle containing the sample and place it in a drying oven that has been pre-aired and heated to 105° C.-110° C., dry it for 1 hour under continuous air blowing conditions, take out the weighing bottle from the drying oven, immediately cover it, put it in a desiccator, cool it to room temperature, and then weigh it.

[0040] M ad =(m1-m2) / m1×100%

[0041] Where: M ad ——Mass fraction of moisture on air-dried basis (%);

[0042] m1——the mass of the air-dried composite iron-coke sample weighed, in grams (g);

[0043] m2 – the mass of the composite ferrocoke sample after drying, in grams (g).

[0044] Compared with the prior art, the present invention has the following beneficial effects:

[0045] The present invention provides a quantitative detection method for composite iron coke, wherein the test items include the contents of total iron, metallic iron, FeO, C, trace elements, SiO2, Al2O3, air-dried basis moisture, dry basis volatile matter and ash in the composite iron coke. The method fully considers the carbon, iron and iron oxide contained in the composite iron coke, excludes the interference of C in the determination of total iron, metallic iron and FeO, considers the influence of these substances when calculating the ash, and then accurately determines the ash and other test items of the composite iron coke, providing an accurate basis for the feeding calculation of the composite iron coke.

[0046] When determining the mass fraction of total iron in the composite iron coke, the present invention firstly performs carbon removal, because the titration endpoint is purple, the composite iron coke has a high carbon content and is black, and black is similar to purple, which affects the judgment of the titration endpoint, so carbon is firstly removed and then the sample dissolution titration is performed; then the composite iron coke particle size is processed into 140 meshes, and such particle size can be completely and quickly dissolved in mixed acid.

[0047] When determining the mass fraction of metallic iron in the composite iron coke, the composite iron coke is processed into a particle size of 140 meshes, and the reaction liquid is filtered with absorbent cotton instead of filter paper and Buchner funnel. This is mainly because the composite iron coke contains a high amount of C. According to the size of the C particle size, the use of absorbent cotton for filtration can block more than 95% of the C. In addition, the absorbent cotton is faster than other filtration speeds and can be completely filtered in about 30 seconds. The filtration speed should be fast to avoid Fe 2+ It can be oxidized by air, causing inaccurate results. Filter paper has a good filtering effect, but the filtering speed is slow and it is easily oxidized by air, causing inaccurate results.

[0048] In the present invention, when determining the mass fraction of FeO in the composite iron coke, NaHCO3 and NaF are added as auxiliary solvents, so that when acidified in isolation from air, the reaction of HCl+NaHCO3=NaCl+H2O+CO2↑ occurs. At the same time, the metal Fe, FeO, Fe3O4, Fe2O3 in the sample reacts with HCl to generate FeCl2, and Fe 2+ It is not easily oxidized in a CO2 atmosphere; then it is cooled to room temperature, quickly filtered with absorbent cotton to remove C, and finally titrated with K2Cr2O7 to remove Fe 2+ Oxidized to Fe 3+ The end point is a purple clear solution, and the titration is completed.

[0049] The present invention adopts infrared carbon-sulfur analysis method when determining the mass fraction of C in composite iron coke, and such test result is more accurate.

[0050] In the present invention, when calculating the composite iron coke ash content, Ad=100-C-metal Fe-FeO-Fe2O3-V d The formula ensures the accuracy of ash content calculation. DETAILED DESCRIPTION

[0051] The present invention is described in detail below with reference to the embodiments.

[0052] The mass solubility of each substance used in the present invention is as follows:

[0053] H2SO4 solution: 1.84 g / mL;

[0054] H3PO3 solution: 1.874 g / mL;

[0055] HCl solution: 1.16 g / mL;

[0056] Copper sulfate solution: 100g / L;

[0057] Ferric oxide standard solution: 20 mg / mL;

[0058] Potassium dichromate solution: 0.05moL / L;

[0059] Nitric acid solution: 1.4 g / mL;

[0060] Hydrofluoric acid solution: 1.13 g / mL;

[0061] Perchloric acid solution: 1.67 g / mL;

[0062] Tin dichloride solution: 60g / L;

[0063] The same composite ferrocoke was measured in the embodiment and the comparative example.

[0064] Example 1

[0065] An industrial analysis and determination method for composite iron coke, the determination method comprising the following test items:

[0066] (1) Determination of total iron (TFe) in composite ferrocoke: The composite ferrocoke was processed into 140 mesh size and then air-dried in an oven at 105°C for 30 minutes to remove moisture. Then, 0.5 g of the sample was weighed into a porcelain square dish and placed in a muffle furnace at 815°C for 30 minutes. The sample was dissolved in 20 mL of sulfuric acid mixed acid composed of H2SO4 solution: H2PO3 solution: H2O in a volume ratio of 3:3:4. The end point was the emission of white phosphoric acid smoke, indicating that Fe, Fe 2+ , Fe4+ Oxidized to Fe 3+ Then add 10mL HCl and then 8 drops of SnCl2 to 3+ Reduction to Fe 2+ , titrate with K2Cr2O7 solution to 2+ Oxidized to Fe 3+ The end point is a purple clear solution, and the titration is completed.

[0067] Mass fraction of total iron (%): TFe = c × (V-V0) × 55.85 × 100 / (m × 1000)

[0068] Where: molar mass of iron in grams per mole (g / mol).

[0069] c—concentration of potassium dichromate standard titration solution, in moles per liter (mol / L);

[0070] V—volume of potassium dichromate standard titration solution consumed by titrating the sample solution, in mL (mL);

[0071] V0—the volume of potassium dichromate standard titration solution consumed by titrating the blank test solution, in mL (mL);

[0072] m—mass of the sample, in grams (g).

[0073] During the measurement process of this project, the particle size of the composite iron coke was also screened. The method was as follows: 0.5 g of composite iron coke of different particle sizes was placed in a muffle furnace and burned at 815°C for 30 minutes, then added to 20 mL of sulfur-phosphorus mixed acid composed of H2SO4:H2PO3:H2O in a volume ratio of 3:3:4, mixed and stirred for 20 minutes, and the dissolution of the composite iron coke was observed. The results are shown in Table 1. It can be seen from the table that when the particle size of the composite iron coke is 140 mesh, its solubility is better, so the composite iron coke of 140 mesh is selected for testing.

[0074] Table 1 Selection of particle size for composite iron coke processing

[0075]

[0076] (2) Determination of metallic iron in composite iron coke: The composite iron coke was processed into 140 mesh size and then air-dried in an oven at 105°C for 30 minutes to remove moisture. Then, 0.5 g of the sample was weighed and placed in a 250 mL glass beaker. 25 mL of water and 25 mL of copper sulfate aqueous solution were added and heated to boil for 15 minutes. Then, boiling water was added to a volume of 50 mL. The sample was then filtered with absorbent cotton. After filtration, deionized water was added to a 250 mL volumetric flask. The sample was tested using an atomic absorption spectrometer. The parameters of the atomic absorption spectrometer were set as follows: absorption wavelength 240.4 nm, lamp current 0.5 mA, incident slit width 0.2 nm, negative high voltage -650 V, and absorption time 3 seconds to obtain the absorbance of metallic iron. The metallic iron content was automatically detected by substituting the linear equation of the working curve.

[0077] 0.5mL, 1.0mL, 2.0mL, 3.0mL, and 4.0mL of ferric oxide standard solution were respectively transferred into a 250mL volumetric flask, which was equivalent to 0.35%, 0.70%, 1.40%, 2.1%, and 2.80% of metallic iron content, and 25mL of copper sulfate solution was added to make up the volume. The atomic absorption spectrometer was used for testing according to the instrument optimization conditions. The parameters of the atomic absorption spectrometer were set as follows: absorption wavelength 240.4nm, lamp current 0.5mA, incident slit width 0.2nm, negative high voltage -650V, absorption time 3 seconds, and the corresponding absorbance was obtained. The working curve was drawn with the metallic iron content as the horizontal coordinate and the absorbance as the vertical coordinate.

[0078] (3) Determination of FeO in composite iron coke: Weigh 0.2 g of a sample with a particle size of 140 mesh, add 2 g of NaHCO3 and 0.5 g of NaF, stir evenly, add 50 mL of concentrated HCl in a 500 mL conical flask, isolate from air and heat to dissolve until the sample bubbles, then cool to room temperature, quickly filter with absorbent cotton, and titrate the filtrate with K2Cr2O7 solution. The endpoint is a purple clear solution, and the titration is complete.

[0079] Mass fraction of FeO (%): ω Fe(Ⅱ) =((V3-V0)×c×M / m0×10 3 )×100-3ω MFe

[0080] Where:

[0081] c—concentration of potassium dichromate standard titration solution, in moles per liter (mol / L);

[0082] V3—the volume of potassium dichromate standard titration solution consumed by the titration sample solution, in mL;

[0083] V0—the volume of potassium dichromate standard titration solution consumed by titrating the blank test solution, in mL (mL);

[0084] m0—mass of the sample, in grams (g);

[0085] M—molar mass of iron in grams per mole (g / mol);

[0086] ω MFe —The metallic iron content of the sample, expressed as mass fraction (%).

[0087] (4) Determination of composite iron coke C: infrared carbon-sulfur analysis method was used, referring to GB / T6730.61-2022 "Determination of carbon and sulfur content of iron ore - High frequency combustion infrared absorption method", 0.05g of sample was weighed, 0.3g of tin particles and 1.5g of tungsten particles were added, and the sample was tested with an infrared carbon-sulfur instrument. 99.99% calcium carbonate standard reagent was selected, and 0.05g, 0.15g, and 0.3g of calcium carbonate standard reagent were weighed respectively, and their infrared absorption energy was detected. The standard curve was drawn through its absorption energy and concentration, and the content of the element to be measured was automatically obtained through the calibration curve from the measured absorption energy.

[0088] (5) Determination of trace elements in composite iron char: including K, Na, Pb, Zn, Cu, Cr, etc. Weigh 0.2g of sample and calcine it in a porcelain square dish at 815℃ for 30min. After cooling to room temperature, transfer the sample in the porcelain square dish to a 100mL plastic beaker. Refer to GB / T6730.62-2017 "Determination of potassium, sodium, vanadium, copper, zinc, lead, chromium, nickel and cobalt content in iron ore - Inductively coupled plasma atomic emission spectrometry". Add 10mL of hydrochloric acid, 2mL of nitric acid, 12 drops of hydrofluoric acid and 5mL of perchloric acid to dissolve until bubbling. Chloric acid smoke for 1-2 minutes, take out and cool to room temperature, rinse with 10mL of water, add 5mL of HCl, make up to volume in a 100mL volumetric flask, shake well, and then use ICP spectrometer to spray the sample for testing. The instrument parameters are set as follows: RF power: 1200W; atomization pressure: 1.0Kpa; auxiliary gas flow: 1.5L / min; peristaltic pump speed: 15r / min; exposure time, long wave exposure time: 5s; short wave exposure time: 15s. The content of the element to be measured is automatically analyzed by the calibration curve based on the measured exposure intensity.

[0089] (6) Determination of SiO2, Al2O3, etc. in composite iron coke: weigh 0.2g of sample and calcine it in a porcelain square dish at 815℃ for 60min. After cooling to room temperature, obtain powder. Then transfer it to a 30mL nickel crucible, add 2g of sodium peroxide, stir evenly, put it into a muffle furnace and heat it at 815℃ for 2-3min to completely dissolve the sample, and then cool it to room temperature. Referring to GB / T6730.63-2006 "Determination of aluminum, calcium, magnesium, manganese, phosphorus, silicon and titanium contents of iron ore - Inductively coupled plasma atomic emission spectrometry", add 50mL of deionized water to the sample, mix concentrated hydrochloric acid and deionized water in a volume ratio of 1:4 to obtain a hydrochloric acid solution, then add 40mL of hydrochloric acid solution to the sample, add deionized water to make the volume up to 200mL, and spray the sample with an ICP spectrometer for testing. The content of the element to be tested is automatically analyzed by the calibration curve based on the exposure intensity measured.

[0090] (7) Determination of air-dried basis moisture of composite iron coke: weigh 1g ± 0.05g of analytical sample with a particle size less than 0.2mm in a weighing bottle that has been dried and weighed in advance, and spread it evenly in the weighing bottle; open the weighing bottle containing the sample and place it in a drying oven that has been pre-aired and heated to 105℃-110℃, and dry it for 1 hour under the condition of continuous air blowing. Take out the weighing bottle from the drying oven, cover it immediately, put it in a desiccator to cool to room temperature (about 20 minutes), and then weigh it.

[0091] M ad =(m1-m2) / m1×100%

[0092] Where: M ad —Mass fraction of moisture on air-dried basis (%);

[0093] m1—the mass of the air-dried composite iron-coke sample weighed, in grams (g);

[0094] m2—The mass of the composite ferrocoke sample after drying, in grams (g).

[0095] (8) Determination of volatile matter on dry basis of composite iron coke: weigh 1 g ± 0.01 g of composite iron coke sample with a particle size of less than 0.2 mm and stir evenly in a covered porcelain crucible that has been pre-burned at 900°C ± 10°C. Then gently shake the crucible to flatten the sample, cover it with a lid, and place it on the crucible stand. Pre-heat the muffle furnace to 900°C ± 10°C, open the furnace door, quickly put the crucible stand with the crucible into the constant temperature zone of the muffle furnace, immediately close the furnace door and start timing, heat accurately for 7 minutes, and the furnace temperature must return to 900°C ± 10°C within 3 minutes, and continue to maintain this temperature until the end of the test. After heating for 7 minutes, immediately remove the crucible from the furnace, cool it in the air for about 5 minutes, move it into a desiccator to cool it to room temperature (about 20 minutes), and then weigh it.

[0096] V ad =(m3-m4) / m3×100%-M ad

[0097] Where: V ad ——Mass fraction of volatile matter on air-dry basis, %

[0098] m3——the mass of the air-dried composite iron-coke sample, in grams (g);

[0099] m4——the mass of the residue after heating the composite iron coke, in grams (g);

[0100] M ad ——Mass fraction of moisture on air-dried basis (%).

[0101] V d =V ad / (100-M ad )×100%

[0102] Where: V d ——Mass fraction of volatile matter on dry basis (%);

[0103] M ad ——Mass fraction of moisture on air-dried basis (%).

[0104] (9) Determination of ash content of composite iron coke:

[0105] Ad=100-mass fraction of C-mass fraction of metal Fe-mass fraction of FeO-mass fraction of Fe2O3-V d , where the mass fraction of Fe2O3 = (mass fraction of total Fe - mass fraction of FeO / 1.2865 - mass fraction of metallic iron) × 1.4296.

[0106] Ad——ash content, in %;

[0107] V d ——Mass fraction of volatile matter on dry basis, in %.

[0108] The contents of various components in the composite iron coke measured according to the method in this example are shown in Table 2.

[0109] Table 2

[0110]

[0111] Comparative Example 1

[0112] An industrial analysis and determination method for composite iron coke, the determination method comprising the following test items:

[0113] (1) Determination of total iron (TFe) in composite iron coke: refer to GB / T6730.65 “Determination of total iron content in iron ore - Titanium trichloride reduction potassium dichromate titration method”;

[0114] (2) Determination of metallic iron in composite iron coke: refer to GB / T6730.6-2016 "Determination of metallic iron content in iron ore - Ferric chloride-sodium acetate titration method";

[0115] (3) Determination of FeO in composite iron coke: refer to GB / T6730.8-2016 "Determination of ferrous content in iron ore - Potassium dichromate titration method";

[0116] (4) Determination of composite iron coke C: refer to GB / T6730.61-2022 "Determination of carbon and sulfur content of iron ore - High frequency combustion infrared absorption method";

[0117] (5) Determination of trace elements in composite iron coke: refer to GB / T6730.62-2017 "Determination of potassium, sodium, vanadium, copper, zinc, lead, chromium, nickel and cobalt content in iron ore - Inductively coupled plasma atomic emission spectrometry";

[0118] (6) Determination of SiO2, Al2O3, etc. in composite iron coke: refer to GB / T6730.63-2006 "Determination of aluminum, calcium, magnesium, manganese, phosphorus, silicon and titanium contents in iron ore - Inductively coupled plasma atomic emission spectrometry";

[0119] (7) Determination of air-dried basis moisture content of composite iron coke: refer to GB / T212-2008 "Industrial analysis and determination methods of coal";

[0120] (8) Determination of volatile matter on dry basis of composite iron coke: refer to GB / T 212-2008 "Industrial analysis methods for coal";

[0121] (9) Determination of ash content of composite iron coke: refer to GB / T 212-2008 "Industrial analysis method of coal"; the contents of various components in the composite iron coke determined by the method in this comparative example are shown in Table 3.

[0122] Table 3

[0123]

[0124] From the comparison between Table 2 and Table 3, it can be seen that Table 3 uses the burning method to calculate the ash content, while Table 2 uses 100-mass fraction of C-mass fraction of metal Fe-mass fraction of FeO-mass fraction of Fe2O3-V dThe ash content is calculated in this way. The main reason why the ash content in Table 3 is 1.53% lower than that in Table 2 is that: since the sample is a composite component containing iron and iron oxides, when placed in a muffle furnace for heating, metallic iron will be oxidized into FeO and Fe2O3, and FeO and Fe3O4 will be oxidized into Fe2O3, resulting in an increase in the mass fraction. Finally, the remaining substances after burning include ash, metallic Fe and iron oxides, and the iron oxides are larger than the actual value, resulting in a decrease in the ash content compared to the actual value (ash content = remaining substances after burning - metallic Fe - iron oxides).

[0125] Table 2 uses chemical analysis and infrared analysis. There is no burning and oxidation. The obtained C, metal Fe, FeO, Vd, and Fe2O3 calculated by TFe, metal Fe, and FeO are all accurate. Ad = 100-mass fraction of C-mass fraction of metal Fe-mass fraction of FeO-mass fraction of Fe2O3-V d Also accurate.

[0126] In order to verify the accuracy of the test results of Example 1 and Comparative Example 1, 10% of composite iron coke was used instead of coke in the blast furnace, and the accuracy of the test results was verified by material balance. 3 For blast furnace, it is calculated that the smelting cycle is 36.9 batches of materials and the time is 5.7 hours when the material line is 1.2m. The average furnace temperature is set to 0.45%. In addition, the raw materials used are guaranteed to be from the same batch, the composition is basically stable, and the operators are fixed. Table 4 2500m 3 After adding composite iron coke to the blast furnace, the material balance table calculated according to the test results in Example 1 is

[0127]

[0128]

[0129] Table 5 2500m 3 After adding composite iron coke to the blast furnace, the material balance table calculated according to the test results in Comparative Example 1

[0130]

[0131]

[0132] Embodiment 1: Through material balance calculation, the blast furnace charging grade is 55.6 °, and the theoretical iron amount of each batch of materials is calculated to be 44.03t, and the amount of slag per ton is 361.6kg. In the blast furnace slag, CaO=41.048%, SiO2=33.345%, Al2O3=15.593%, MgO=8.741%, and in the molten iron, S=0.0298%, P=0.141%, As=0.0127%, Sn=0.0050%, Cu=0.02926%, and Cr=0.0306%.

[0133] Comparative Example 1: Through material balance calculation, the blast furnace charging grade is 55.6°, the theoretical iron amount of each batch of materials is calculated to be 44.03t, the amount of slag per ton of iron is 361.5kg, CaO=41.051%, SiO2=33.339%, Al2O3=15.588%, MgO=8.743% in the blast furnace slag, S=0.0298%, P=0.141%, As=0.0127%, Sn=0.0050%, Cu=0.02782%, Cr=0.0306% in the molten iron.

[0134] After adding the raw materials and a smelting cycle of about 5.7 hours, the chemical compositions of molten iron and slag were Si=0.45%, S=0.029%, P=0.141%, As=0.0130%, Sn=0.0048%, Cu=0.03017%, Cr=0.0316%, CaO=41.043%, SiO2=33.349%, Al2O3=15.597%, and MgO=8.733%.

[0135] Conclusion: By comparing with the actual composition of molten iron and slag, it is concluded that the composition of molten iron and slag obtained by theoretical material balance in Example 1 is very close to the actual situation, and Example 1 is closer to the actual composition of molten iron and slag than Comparative Example 1, especially the Cu element. The deviation between the comparative example and the actual one is large. It can be seen that the industrial analysis and determination method of composite iron coke provided by the present invention has high accuracy.

[0136] The detailed description of an industrial analysis and determination method for composite ferrocoke with reference to the above-mentioned embodiment is illustrative rather than restrictive, and several embodiments can be listed according to the limited scope. Therefore, changes and modifications without departing from the overall concept of the present invention should fall within the scope of protection of the present invention.

Claims

1. An industrial analysis and determination method for composite iron coke, characterized in that: The determination method includes the following test items: (1) Determination of total iron content: Grind the composite iron coke, remove moisture, burn and dissolve a quantitative sample, and titrate with potassium dichromate; (2) Determination of metallic iron content: Grind the composite iron coke to remove moisture, react a quantitative sample with a copper sulfate solution, and filter it using absorbent cotton. The resulting filtrate is tested by an atomic absorption spectrometer. (3) Determination of FeO content: Mix a quantitative sample with sodium bicarbonate and sodium fluoride, isolate the sample from air, add concentrated hydrochloric acid to dissolve the sample, and then filter it with absorbent cotton. The filtrate is titrated with potassium dichromate. (4) C content determination: using infrared carbon-sulfur analysis method, the sample is mixed with tin particles and tungsten particles and tested with an infrared carbon-sulfur instrument; (5) Trace element determination: The sample is burned, dissolved, fixed to volume, and then detected using an ICP spectrometer; (6) Determination of SiO2 and Al2O3: Mix the sample with sodium peroxide after burning, then burn and dissolve it. After cooling, add deionized water and hydrochloric acid solution to make up the volume, and then use ICP spectrometer for detection; (7) Determination of air-dried basis moisture: Dry a certain amount of sample in a blast drying oven, and calculate the mass fraction of air-dried basis moisture based on the mass before and after drying; (8) Determination of volatile matter on dry basis: Determination shall be carried out in accordance with the method for determination of volatile matter in GBT 212-2008 Industrial analysis method for coal; (9) Ash content determination: ash mass fraction = 100 - mass percentage of C - mass percentage of metallic iron - mass percentage of FeO - mass percentage of Fe2O3 - mass percentage of volatile matter on a dry basis.

2. The industrial analysis and determination method of composite iron coke according to claim 1, characterized in that: The method for determining the total iron content is as follows: grinding the composite iron coke into 140 mesh particles and drying to remove moisture; accurately weighing a certain mass of the composite iron coke and calcining it at 810-820° C. for 25-35 minutes; dissolving the calcined sample using mixed acid, and after white smoke comes out of the sample, adding hydrochloric acid and tin chloride in sequence, and then titrating with potassium dichromate until the solution turns purple, and calculating the mass fraction of the total iron according to the concentration of potassium dichromate and the volume consumed in the titration.

3. The industrial analysis and determination method of composite iron coke according to claim 2, characterized in that: The mixed acid is a mixed solution of sulfuric acid, phosphoric acid and water in a volume ratio of 3:3:

4.

4. The industrial analysis and determination method of composite iron coke according to claim 1, characterized in that: The method for determining the metallic iron content is as follows: grinding the composite iron coke into 140 mesh particles, drying to remove moisture; accurately weighing a certain mass of the composite iron coke, mixing it with deionized water and copper sulfate solution, heating and boiling for 10 to 20 minutes, then filtering it with absorbent cotton, collecting the filtrate and detecting it with an atomic absorption spectrometer; mixing a series of concentrations of ferric oxide standard solutions with copper sulfate solution, constructing a standard curve with atomic absorption spectrometer detection, and calculating the metallic iron content based on the standard curve.

5. The industrial analysis and determination method of composite iron coke according to claim 1, characterized in that: The method for determining the FeO content is as follows: uniformly mixing a certain amount of composite iron coke with sodium bicarbonate and sodium fluoride, adding concentrated hydrochloric acid to dissolve the sample, then filtering with absorbent cotton, titrating the obtained filtrate with potassium dichromate until the solution turns purple, and calculating the mass fraction of FeO according to the concentration of potassium dichromate and the volume consumed in the titration.

6. The industrial analysis and determination method of composite iron coke according to claim 1, characterized in that: The method for determining C is: using infrared carbon-sulfur analysis, weighing 0.05g of sample, adding 0.3g of tin particles and 1.5g of tungsten particles, detecting with an infrared carbon-sulfur instrument, and analyzing the results using a calibration curve.

7. The industrial analysis and determination method of composite iron coke according to claim 1, characterized in that: The method for determining the trace elements is as follows: weigh 0.2 g of a sample and burn it at 815° C. for 30 min. After cooling to room temperature, add 10 ml of hydrochloric acid, 2 ml of nitric acid, 0.5 ml of hydrofluoric acid, and 5 ml of perchloric acid to dissolve until thick perchloric acid smoke is emitted for 1-2 min. Take out and cool to room temperature, add 5 ml of HCl to make up the volume, and then detect with an ICP spectrometer and analyze the results using a calibration curve.

8. The industrial analysis and determination method of composite iron coke according to claim 1, characterized in that: The method for determining SiO2 and Al2O3 is as follows: weigh 0.2g of the sample and calcine it in a porcelain square dish at a constant temperature of 815°C for 60min, cool it to room temperature to obtain a powder, then transfer it to a 30mL nickel crucible, add 2g of sodium peroxide, stir evenly, put it into a muffle furnace and heat it at a constant temperature of 815°C for 2-3min to completely dissolve the sample, and cool it to room temperature; add 50mL of deionized water to the sample, mix concentrated hydrochloric acid and deionized water in a volume ratio of 1:4 to obtain a hydrochloric acid solution, then add 40mL of the hydrochloric acid solution to the sample, add deionized water to make the volume up to 200mL, and detect it using an ICP spectrometer.

9. The industrial analysis and determination method of composite iron coke according to claim 1, characterized in that: The method for determining the moisture content on an air-dried basis is as follows: weigh 1 g ± 0.05 g of an analytical sample with a particle size of less than 0.2 mm and spread it evenly in a weighing bottle, open the weighing bottle containing the sample and place it in a drying oven that has been pre-aired and heated to 105° C.-110° C., dry it for 1 hour under continuous air blowing conditions, take out the weighing bottle from the drying oven, immediately cover it, put it in a desiccator, cool it to room temperature, and then weigh it.